Effects of body composition and basal metabolic rate the temporal parameters of ground reaction forces on gait of postmenopausal women - Sousa, Adriana Leite (2020)
Objective: The study aims to identify and analyze the influence of body composition and basal metabolic rate over the behavior of temporal parameters of ground reactive forces during the gait of postmenopausal. Methods: The experimental study was carry out with 52 women (±59.8 years). The fat mass, abdominal visceral adiposity, skeletal muscle mass, fat-free mass and basal metabolic rate have evaluated by octopolar bioimpedance. The data for the ground reactive forces were collect through the force platform. Results: In relative terms, the fat mass showed influence the final phase of support, causing a decrease in this parameter. Abdominal visceral adiposity also exerted inverse influence on the vertical loading (r = -0.31) and unloading (r = -0.35) rate. The skeletal muscle mass (r = -0.45, r = -0.46; p<0.01) and basal metabolic rate (r = -0.44, r = -0.46; p<0.01) influenced the vertical loading rate and the relationship between the vertical rates significantly. Conclusion: The study suggests that the increase on fat mass and abdominal visceral adiposity, influence the support time and the vertical rates. With a more robust skeletal muscle system the postmenopausal women exhibit the phases of the gait cycle less accentuated, signaling less stress on the joints.